Pediatric colonoscopy in South China: a 12-year experience in a tertiary center. - Pingguang Lei; Fang Gu; Liru Hong; Yuli Sun; Minrui Li; Huiling Wang; Bihui Zhong; Minhu Chen; Yi Cui; Shenghong Zhang (PLoS ONE, 2014)
Objective To investigate: 1) the demographics and clinical characteristics, 2) the findings, and 3) the safety and effectiveness in a cohort of Chinese pediatric patients undergoing colonoscopy. Methods The study participants were consecutive patients aged ≤14 years old that underwent their first colonoscopy in the endoscopy center at the First Affiliated Hospital, Sun Yat-sen University between Jan. 1, 2001 and Dec. 31, 2012. Demographic, clinical, endoscopic, and pathological findings were collected. Results The cohort consisted of 322 patients, including 218 boys (67.7%) and 104 girls (32.3%). The median age was 8.0 years old and ranged from 9 months to 14 years old. Hematochezia (48.8%) and abdominal pain/discomfort (41.3%) were the most common presentations preceding pediatric colonoscopy. The caecal intubation success rate was 96.3%. No serious complications occurred during the procedures. A total of 227 patients (70.5%) received a positive diagnosis under endoscopy, including 138 patients with polyps and 53 patients with inflammatory bowel disease (IBD). Among the patients with polyps, 71.0% were juvenile polyps. Comparisons between years 2001-2006 and 2007-2012 showed that the IBD detection rate increased significantly (4.6% vs. 22.4%, P<0.001), while the opposite occurred for the polyp detection rate (73.1% vs. 27.6%, P<0.001). Conclusion Colonoscopy in pediatric patients is a safe and effective procedure. Polyps are the primary finding during colonoscopy. In South China there has been an increase in pediatric patients diagnosed with IBD over the past decade. However, a large epidemiological study is needed to confirm our findings.